Mechanically exfoliated 2D nanomaterials as saturable absorber for Q-switched erbium doped fiber laser - Ahmed, Mahmoud Hazzaa M.; Al-Masoodi, Ahmed Hasan Hamood; Latiff, Anas Abdul; Arof, Hamzah; Harun, Sulaiman Wadi (Springer Verlag (Germany), 2017)
We experimentally demonstrate a passive, stable and low cost Q-switched erbium-doped fiber laser based on molybdenum disulfide (MoS2) and black phosphorus (BP) saturable absorber (SA). Both MoS2 and BP SAs are prepared by mechanically exfoliating the crystal and fixing the acquired flakes onto the end surface of a standard FC/PC fiber connector. By integrating either MoS2 or BP SA into the laser cavity, a stable Q-switched operation is achieved at wavelengths of 1551.4 or 1552.9 nm respectively. Using the MoS2 SA, the repetition rate of the output laser increases from 14.25 to 38.43 kHz as the 980 nm pump power rises from 57 to 170 mW while its pulse width reduces from 10.7 to 5.02 μs. The maximum pulse energy was 141.3 nJ. On the other hand, with the BP SA, the repetition rate and pulse width fall in the ranges of 9.1–44.33 kHz and 20.75–7.04 μs respectively, as the pump power grows from 50 to 170 mW. The laser with the BP SA, produces the maximum pulse energy of 134 nJ. The experimental results indicate that MoS2 and BP SAs can be used to generate stable Q-switching pulses at 1.5 μm region successfully.